Risk connectivity and risk mitigation: An analytical framework - Soumyatanu Mukherjee; Sidhartha S. Padhi (The University of Nottingham, Centre for Research in Economic Development and International Trade (CREDIT), 2018)
This paper studies the decision problem of risk averse single-output producers and suppliers under uncertainties in input prices, in a two-moment decision model with the presence of a dependent background risk. This framework is based on the utility from the expected value and the standard deviation of the uncertain random total profit of the supplier. Our theoretical framework for studying producers' responses to risks allows not only for analysing risk averse suppliers' attitude towards endogenous and background risks, but also to identify how the changes in the connectivity (i.e. correlation) between these two broad sources of risks will affect the risk averse suppliers' decision at the optimum. All comparative static effects are described in terms of the relative sensitivity of the supplier towards risks. This analytical framework has a number of potential application in development economics, such as optimal production decision under energy price uncertainty, output price uncertainty, and exchange rate uncertainty.
Keywords: D21; D81; 330; Supply chain management; Risk management; two-moment decision model; background risk